2020
DOI: 10.1111/geb.13188
|View full text |Cite
|
Sign up to set email alerts
|

Relative impacts of land‐use and climate change on grasshopper range shifts have changed over time

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
52
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(58 citation statements)
references
References 64 publications
(171 reference statements)
6
52
0
Order By: Relevance
“…Almost all species actively colonize transformed habitats such as lawns, roadsides, and agricultural fields [114]. Similar combination of some positive and negative trends in orthopteran diversity and distribution changes mainly associated with local human activity is also revealed for Central European grasslands [130,131] and the mountains of Switzerland [132]. On the contrary, our unpublished data show that the distribution of orthopteran taxa and populations over the steppe intermountain basins of the Altay-Sayan Mountains remains relatively stable.…”
Section: Conclusion: the Steppe Orthoptera-retrospective And Prospectivesupporting
confidence: 68%
“…Almost all species actively colonize transformed habitats such as lawns, roadsides, and agricultural fields [114]. Similar combination of some positive and negative trends in orthopteran diversity and distribution changes mainly associated with local human activity is also revealed for Central European grasslands [130,131] and the mountains of Switzerland [132]. On the contrary, our unpublished data show that the distribution of orthopteran taxa and populations over the steppe intermountain basins of the Altay-Sayan Mountains remains relatively stable.…”
Section: Conclusion: the Steppe Orthoptera-retrospective And Prospectivesupporting
confidence: 68%
“…6 Mean number of individuals (± 95% CI) per transect of the 10 most abundant species shown separately for grazed and mown transects. Asterisks indicate significant differences in abundance between mown and grazed transects (t-test; *p ≤ 0.05, **p ≤ 0.01, ***p ≤ 0.001, ****p ≤ 0.0001) Austria (Zuna-Kratky et al 2017) and Central Europe in general (Poniatowski et al 2020) in response to climate warming.…”
Section: Effects Of Grazing Vs Mowing On Orthoptera Assemblagesmentioning
confidence: 99%
“…Recent studies revealed that insect species with low dispersal ability will hardly be able to cope with climate change in fragmented landscapes (Pöyry et al ., 2009; Poniatowski et al ., 2020). According to the low mobility of L. helle (Fischer et al ., 1999), this might especially apply to its central European populations which are mostly restricted to low‐mountain ranges (Kudrna et al ., 2011; Wachlin, 2020).…”
Section: Implications For Conservationmentioning
confidence: 99%